2022
DOI: 10.3389/fimmu.2022.952987
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and systems biology approach to identify the pathogenetic link of Long COVID and Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: Background: The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a global crisis. Although many people recover from COVID-19 infection, they are likely to develop persistent symptoms similar to those of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) after discharge. Those constellations of symptoms persist for months after infection, called Long COVID, which may lead to considerable financial burden and healthcare challenges. However, the mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…Transcription factors (TFs) are proteins that can bind to specific DNA sequences and regulate gene expression ( 43 ). MicroRNAs (miRNAs) are a class of endogenous short non-coding RNAs that mediate the degradation of target mRNAs or repress translation ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…Transcription factors (TFs) are proteins that can bind to specific DNA sequences and regulate gene expression ( 43 ). MicroRNAs (miRNAs) are a class of endogenous short non-coding RNAs that mediate the degradation of target mRNAs or repress translation ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although there are no studies directly proving that acute COVID-19 triggers ME/CFS, several studies have identified multiple overlapping or similar symptoms between long COVID and ME/CFS [ 127 ]. COVID-19 also greatly increases the number of patients with ME/CFS [ 128 ], and bioinformatics analysis has identified a common network of genetic interactions between the two [ 129 ]. According to the diagnostic criteria for ME/CFS, the overall prevalence of ME/CFS was as high as 43% among patients with long COVID, with fatigue, malaise on exertion, and insomnia representing the main symptoms [ 130 ].…”
Section: Therapeutic Potential Of Naringin and Naringenin In Long Covidmentioning
confidence: 99%
“… 89 , 98 The widespread inflammatory response triggered by SARS-CoV-2 infection has been reported in patients with varying degrees of illness severity, 80 , 99 which could occur in the nervous system and contribute to neuropsychiatric symptoms. 80 , 83 The interaction networks of ME/CFS and long COVID, including inflammatory cytokines comprising interleukin (IL)-6 and IL-1B, common genes, and microRNAs, have recently been depicted, 100 revealing the potential mechanism of ME/CFS in the occurrence of long COVID and further emphasizing the significance of the inflammatory response. Meanwhile, the dysregulation of endothelin-1 has been found in long COVID patients and cases presenting exertion intolerance and persistent fatigue, suggesting the emergence of endothelial dysfunction and its effect on ME/CFS.…”
Section: Symptoms and Possible Mechanismsmentioning
confidence: 99%